2023
DOI: 10.1111/geb.13652
|View full text |Cite
|
Sign up to set email alerts
|

Linking seed size and number to trait syndromes in trees

Abstract: Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Volatility can also be used in comparative species-or populationlevel studies, but in those cases, it will require the estimation of absolute values of annual seed production (Qiu et al, 2023). This is now possible using the mastif model that accommodates both seed trap and crop count data to estimate absolute seed production of individual trees (Clark et al, 2019;Journé et al, 2022;Bogdziewicz et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volatility can also be used in comparative species-or populationlevel studies, but in those cases, it will require the estimation of absolute values of annual seed production (Qiu et al, 2023). This is now possible using the mastif model that accommodates both seed trap and crop count data to estimate absolute seed production of individual trees (Clark et al, 2019;Journé et al, 2022;Bogdziewicz et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, we tested whether processes (such as pollination or seed consumption) are related to masting patterns (such as volatility or synchrony) once temporal patterns in the latter were extracted. Further details on the GJAM fitting and conditional predictions can be found in Qiu et al (2021) and Bogdziewicz et al (2023).…”
Section: Masting Breakdownmentioning
confidence: 99%
“…In summary, our analysis supports the idea that the extent of year-to-year variation in masting is regulated by a species’ phylogeny, location (climate), and life history (plant form). The effects of climate and phylogeny on mast seeding and functional traits necessitated conditional predictions that extracted direct associations 27 , 28 . A PCA analysis that combined all the ways in which variables can be linked suggested that masting created a third, mostly independent dimension of variation in plant traits.…”
Section: Discussionmentioning
confidence: 99%
“…The GJAM allowed us to accommodate the dependence between traits and phylogeny as random groups. To this end, we followed past studies that used a similar approach 27 , 67 , and grouped species according to genus or family (when the genus had <10 species). We used the ’multiple’ category for families with <5 species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation